2018
DOI: 10.12681/jhvms.15490
|View full text |Cite
|
Sign up to set email alerts
|

Effects of concomitant selenium and vitamin E administration on thyroid hormone metabolism in broilers

Abstract: ABSTRACT.A total of 400, as hatched, broilers were used to investigate the effect of selenium (Se) and vitamin E supplementation on thyroid hormones metabolism. There were 5 replicates of 4 dietary treatments namely: control (C), a soybean meal maize basal diet with adequate Se and vitamin E (0.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…The results of triiodothyronine (T 3 ) agree with Srimongkol (2003), Upton et al (2008) and El-Sheikh et al (2010) who indicated that triiodothyronine (T 3 ) hormone was significantly (P<0.05) increased in broiler fed selenium supplementation compared to those fed a basal diet. On contrary, Pappas et al (2017) concluded that supplementation with selenium alone or in combination with vitamin E in broiler diets above their requirements did not affect thyroid hormone metabolism. Therefore, Dönmez et al (2001) reported that serum triiodothyronine level was significantly reduced with high zinc levels (500 and 1000 mg Zn as ZnSO 4 / L of drinking water) of zinc intake.…”
Section: Blood Biochemical Profilesmentioning
confidence: 94%
“…The results of triiodothyronine (T 3 ) agree with Srimongkol (2003), Upton et al (2008) and El-Sheikh et al (2010) who indicated that triiodothyronine (T 3 ) hormone was significantly (P<0.05) increased in broiler fed selenium supplementation compared to those fed a basal diet. On contrary, Pappas et al (2017) concluded that supplementation with selenium alone or in combination with vitamin E in broiler diets above their requirements did not affect thyroid hormone metabolism. Therefore, Dönmez et al (2001) reported that serum triiodothyronine level was significantly reduced with high zinc levels (500 and 1000 mg Zn as ZnSO 4 / L of drinking water) of zinc intake.…”
Section: Blood Biochemical Profilesmentioning
confidence: 94%